Wnt and FGF mediated epithelial‐mesenchymal crosstalk during lung development. Issue 3 (29th December 2014) - Volckaert, Thomas; De Langhe, Stijn P.; Trainor, Paul; Johnson, Randy
ABSTRACT Background: The adaptation to terrestrial life required the development of an organ capable of efficient air‐blood gas exchange. To meet the metabolic load of cellular respiration, the mammalian respiratory system has evolved from a relatively simple structure, similar to the two‐tube amphibian lung, to a highly complex tree‐like system of branched epithelial airways connected to a vast network of gas exchanging units called alveoli. The development of such an elaborate organ in a relatively short time window is therefore an extraordinary feat and involves an intimate crosstalk between mesodermal and endodermal cell lineages. Results: This review describes the molecular processes governing lung development with an emphasis on the current knowledge on the role of Wnt and FGF signaling in lung epithelial differentiation. Conclusions: The Wnt and FGF signaling pathways are crucial for the dynamic and reciprocal communication between epithelium and mesenchyme during lung development. In addition, some of this developmental crosstalk is reemployed in the adult lung after injury to drive regeneration, and may, when aberrantly or chronically activated, result in chronic lung diseases. Novel insights into how the Wnt and FGF pathways interact and are integrated into a complex gene regulatory network will not only provide us with essential information about how the lung regenerates itself, but also enhance our understanding of the pathogenesis of chronic lung diseases, as well as improve the controlled differentiation of lung epithelium from pluripotent stem cells. Developmental Dynamics 244:342–366, 2015. © 2014 Wiley Periodicals, Inc.